Global, regional, and national years lived with disability due to blindness and vision loss from 1990 to 2019: Findings from the Global Burden of Disease Study 2019 - Li, Shasha; Ye, Enlin; Huang, Jiasheng; Wang, Jia; Zhao, Yumei; Niu, Dongdong; Yue, Suru; Huang, Xueying; Liu, Jie; Hou, Xuefei; Wu, Jiayuan (Frontiers in Public Health, 2022)
Purpose This study aimed to provide a comprehensive assessment of burden estimates and the secular trend of blindness and vision loss, as measured by years lived with disability (YLDs), at the global, regional, and national levels. Methods The age-standardized YLD rates (ASYRs) due to blindness and vision loss and its subtypes, including moderate vision loss, severe vision loss, blindness, and presbyopia, from 1990 to 2019 were extracted from the Global Burden of Disease Study 2019 database. The estimated annual percentage changes (EAPCs) were calculated to quantify the temporal trends in the ASYRs due to blindness and vision loss. Results In 2019, the global ASYRs per 100,000 population was 327.98 for blindness and vision loss, specifically, 85.81 for moderate vision loss, 74.86 for severe vision loss, 95.03 for blindness, and 62.27 for presbyopia. From 1990 to 2019, the ASYRs due to blindness and vision loss slightly decreased. Females showed higher ASYRs than males in 2019. The global highest ASYRs were observed in South Asia and sub-Saharan Africa. Negative associations were found between the burden estimates of blindness and vision loss and the sociodemographic index levels. The EAPCs of ASYRs in blindness and vision loss were significantly negatively correlated with the ASYRs in 1990 and positively correlated with human development indices in 2019. Conclusions Globally, blindness and vision loss continue to cause great losses of healthy life. Reasonable resource allocation and health-service planning are needed for the prevention and early intervention of disabilities caused by vision loss.